Cell Wall Structure of Coccoid Green Algae as an Important Trade-Off Between Biotic Interference Mechanisms and Multidimensional Cell Growth - Dunker, Susanne; Wilhelm, Christian (Frontiers in Microbiology, 2018)
Coccoid green algae can be divided in two groups based on their cell wall structure. One group contains a highly chemical resistant cell wall (HR-cell wall), consisting of the biopolymer algaenan. Tthe other group is more susceptible to chemicals and lacks the biopolymer algaenan (LR cell wall – Low resistant cell wall). Algaenan is considered as important molecule to explain cell wall resistance. Interestingly,These cell wall properties types (LR- and HR-cell wall) are not in accordance with the taxonomic classes Chlorophyceae and Trebouxiophyceae, which makes it even more interesting to consider the ecological function. It was already shown that algaenan helps to protect against virus, bacterial and fungal attack, but in this study we show for the first time that green algae with different cell wall properties show different sensitivity against interference competition with the cyanobacterium Microcystis aeruginosa. Based on previous work with co-cultures of M. aeruginosa and two green algae (Acutodesmus obliquus and Oocystis marssonii) differing in their cell wall structure, it was shown that M. aeruginosa could impair only the growth of the green algae if they belong to the LR-cell wall type. In this study it was shown that the sensitivity to biotic interference mechanism shows a more general pattern within coccoid green algae species depending on cell wall structure.